DEVELOPMENT AND VALIDATION OF A STABILITY-INDICATING RP-HPLC METHOD FOR THE ESTIMATION OF METFORMIN, SAXAGLIPTIN, AND DAPAGLIFLOZIN - KONDETI, HARITHA PAVANI; SANKAR DANNANA, GOWRI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: A new combination of Metformin, Saxagliptin, and Dapagliflozinfixed-dose combination of antidiabetic medication is being used as an adjunct to diet and exercise to improve glycemic control in adults with type 2 diabetes. Methods: Chromatography was carried out using Kromasil C18 250×4.6, 5.0 mm column with a flow rate of 1.0 ml/min. The mobile phase comprised of pH 4.8 0.01 N Potassium dihydrogen phosphate buffer and Acetonitrile in the ratio of 65:35 is used. The developed method has been validated for various parameters such as precision, accuracy, linearity, robustness, limit of detection (LOD), limit of quantification (LOQ), and solution stability. The stability-indicating capability of the method was established by forced degradation studies under stress conditions such as acid, base, peroxide, UV, thermal, and humidity. Results: The retention times of Metformin, Saxagliptin, and Dapagliflozin were found to be 2.294, 2.869, and 3.887 min, respectively. The method was specific and linear (R2>0.999) for MET, SXG, and DGF. The LOD and LOQ were found to be 13.85 μg/ml and 41.95 μg/ml for MET, 0.06 μg/ml and 0.19 μg/ml for SXG and 0.19 μg/ml and 0.57 μg/ml for DGF, respectively. The mean % recovery obtained was found to be 100.21% for MET, 99.83% for SXG, and 99.97% for DGF, respectively. Conclusion: Hence, the chromatographic method developed was said to be rapid, simple, specific, sensitive, precise, accurate, robust, and reliable that can be effectively applied for routine analysis in research institutions, quality control departments in industries.